Kepemimpinan Perempuan sebagai Kepala Perangkat Daerah di Lingkungan Pemerintah Daerah Kabupaten Bandung Barat - Miftakhul Setiavani (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
This research has been done in 3 Agencies who’s led by the woman as the Head of Agency, specifically in Archival and Library Services, Department of Tourism and Culture, and Civil Service Police Unit and Fire Brigade Units. The goal of this research is to get an overview about the woman’s characteristics in leadership, consists of 4 factors as the mother, the pet, the sex and the iron maiden in their duty as The Head of Agency. This research is held to determine factors that hinder in women’s leadership and how to manage it. The method in this research is qualitative and explained descriptively with an inductive approach. The data collection technique is by conducting observation, semi-structured interviews with 17 informants and documentation. In analyzing the data, techniques that is used is data collection, data reduction, data analyzing and draw conclusions. Result from this research are those 4 factors had been found in all woman’s Head of Agencies but with one dominant factor in each of woman’s leader. The obstacle in women’s leadership as The Head of Agency is a negative view at the women’s leadership itself, discrimination of individual problem and lack of discipline in employees. As for resolving those obstacles, West Bandung Regency Government appeal to all employees to increase tolerance, increase the application of Gender Mainstreaming and to increase exemplary of leaders.